β-cyclodextrins : an eco friendly contribution to textile finishing - Soares, Graça M. B. (2010)
β-Cyclodextrins (CD) has been assuming grow interest as eco friendly auxiliary products in textile finishing. As agent in surface modification of materials, contributes to the functional textiles production, important in “traditional” uses but essential to new technical applications such cosmetic and well-being with high specificity. Their use can as well allows the application processes optimization or new aesthetic effects in dyeing or printing products. Present communication aims discuss new dyeing applications using β-cyclodextrin derivative as modifier agent of dyes properties. To that, the application of insoluble dyes to produce fluorescent or dyed materials with special colour effects are described and all parameters that could influence the dyeing process were detailed analyzed. The dyes–CD interaction strategy to dissolve the dyes contributes to the design of new and more ecological dyeing application processes of cellulosic textile materials.